Keabsahan Surat Edaran Yang Muatan Materinya Bersifat Pengaturan Dan Sanksi - Pattinasarany, Yohanes (Jurnal Saniri, 2022)
Today's increasingly rapid development of government practices, the government often makes circular laws which are used as the legal basis for legalizing government actions or actions in certain areas of government affairs. However, the act of forming a circular letter in question sometimes creates legal problems because it is not in accordance with the nature of the circular letter in question because the material content of the circular letter is of a general regulatory nature and even contains legal sanctions. Even though the existence of a Circular Letter as part of a policy regulation that contains information or official notices that are technical guidelines in carrying out a government affair. The contents of a Circular Letter are organizational internal technical guidelines, which are different from Laws and Regulations which contain generally accepted regulatory material (into and outside the scope of the institution that makes it) and contain sanctions as a form of coercive power, so that if there is a circular letter whose material content is regulations and contains sanctions, the circular letter is considered to have no validity, because it is not in accordance with its nature, function and position.